Al-Hajjaj in the Arabic Grammar Book Dr. Ibrahim Al-Samarrai - Taha, Mayassa Waleed (Al-Adab Journal, 2022)
The rational nature of Arabic grammar imposes Hajjaj ( The argumentative ) aspect on everyone who rejects the logical grammarians’ opinions or tries to renew in its chapters in an effort to facilitate it. Among these attempts is the book of Grammar . Which it is constructed and criticized by Dr. Ibraheem Al-Samarrai.The research monitored Hajjaj methods on which the Arabic grammar book was built as criticism and construction . Which is a criticism based on rejection, discussion and dialogue for a grammatical intellectual construct that views language as a science that simulates other sciences in its development and renewal . This is governed by the philosophical thought that adopted by the grammarians in their writings . As they were influenced by the discussions of the fundamentalists and speakers' analytics.This study came on two axes . Firstly : Dealing with the methods of Hajjaj and the other : dealing with the manifestations of Al – Hajjaj . It is based on the saying of Al-Samarrai: (( In this research I conducted a criticism of the old grammar to show what it contains of materials and methods that are not from it . And to state to the reader on what can be knows it from grammatical science in order to distinguish between correct and incorrect )) . Which reveals his protest against the opinions of the ancients according to what is governed by modern linguistic usage.